The Effect Of Coiling Exercises On Tennis Spin Serve - Ians Aprilo (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
The main problem that arises is that service is only considered as the beginning of a match. Serving is a very important thing in a match because serving is a fast way to get points. One important part of the tennis serve is the skill of coiling or body rotation. The purpose of this study was to analyze the increase in coiling exercise tennis spin serve. The research method used was quantitative descriptive with 30 South Sulawesi beginner tennis athletes aged between 14-16 years as subjects. The research was conducted at the Tennis Court, Faculty of Sports Science, Makassar State University, for 8 weeks, in the first week the coiling tennis spin serve pretest was carried out and in the last week the coiling tennis spin serves post-test was carried out which was analyzed using Kinova. This coiling training is carried out a frequency of 3 times per week. The results of this study are an average increase of 1,267. So it can be concluded that coiling exercise can improve tennis spin serve in South Sulawesi novice athletes.